2017
DOI: 10.1111/grow.12204
|View full text |Cite
|
Sign up to set email alerts
|

Energy Boom and Gloom? Local Effects of Oil and Natural Gas Drilling on Subjective Well‐Being

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…For example, in an analysis of letters to the editor about UNGD in a newspaper in Pennsylvania, stress was a major theme 2 , and a sample of people living near UNGD reported stress as their most common symptom 38 . In Texas, Maguire and colleagues used county-level Behavioral Risk Factor Surveillance System data and found an association between UNGD and reduced life satisfaction among women and an increased number of poor mental health days among both sexes 26 . Perceived changes in quality of life 30 , 39 , 40 , health effects 29 , or resource loss 25 , as well as feelings of disempowerment 31 , 41 , a disrupted sense of place 25 , 27 , and a loss of community cohesion 10 , 25 could potentially explain our observed association between UNGD activity and depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an analysis of letters to the editor about UNGD in a newspaper in Pennsylvania, stress was a major theme 2 , and a sample of people living near UNGD reported stress as their most common symptom 38 . In Texas, Maguire and colleagues used county-level Behavioral Risk Factor Surveillance System data and found an association between UNGD and reduced life satisfaction among women and an increased number of poor mental health days among both sexes 26 . Perceived changes in quality of life 30 , 39 , 40 , health effects 29 , or resource loss 25 , as well as feelings of disempowerment 31 , 41 , a disrupted sense of place 25 , 27 , and a loss of community cohesion 10 , 25 could potentially explain our observed association between UNGD activity and depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are beginning to find significant psychosocial and mental health outcomes related to UOG production, outcomes that are particularly deleterious for individuals living in a “fracking community” [ 64 ]. Micro-level impacts of UOG production may include: systemic loss of trust in leaders, industry operators, and neighbors; persistent feelings of concern about environmental degradation; concerns about pollutants and potential health risks; and general mental distress [ [65] , [66] , [67] ]. Meso-level manifestations of psychological stress and poor mental health outcomes related to UOG production include: ‘collective trauma’ and loss of community unity, lifeways, and social fabrics [ [55] , [68] , [69] ]; social disruption from boom and bust cycles [ 70 ]; gendered imbalances [ 71 ] and distressing and alienating working conditions [ 72 ], especially for male workers [ [64] , [73] ]; increased sex trafficking around oil and gas ‘mancamps’, which can particularly affect Indigenous women [ [74] , [75] ]; and various disparities in resource and information access between industry and people living amid drilling [ 76 ].…”
Section: A Review: Industrial Environmental Stressors Environmental mentioning
confidence: 99%
“…More recently, Maguire and Winters () reported that sampled local residents had experienced negative effects from horizontal oil and gas drilling outside the Dallas‐Fort Worth metropolitan area in Texas. The residents perceived that their well‐being was reduced because the costs of horizontal drilling were greater than the benefits.…”
Section: Energy Boom and Crimesmentioning
confidence: 99%